Eclectic Hermeneutic Method: A Philosophical Study - Habsy, Bakhrudin All (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2020)
The method of Eclectic hermeneutics is one type of qualitative research aimed at understanding and interpreting literalism in depth and making appropriate articulation as the capture and interpretation of meanings based on the elements, as well as understanding the elements based on the overall meaning. The eclectic hermeneutics method is a methodological procedure for the practice of the interpretation of literalism of the fourth level which reaches reflexive or quadri hermeneutics interpretation and interpretation. By applying the eclectic hermeneutic method, the understanding and interpretation of networks of meaning or structure of literalism symbols can be broad, flexible, wise, inclusive, contextual, actual, open-ended system, humanistic, transformative, liberative and emancipatory based on awareness, depth of understanding intersubjective and clarity of interpretation of the interpreter of the focus and purpose of research. This study aims to foster and restore the sophistication of hermeneutics at its base as a scientific method in understanding and interpreting the literary traditions in various cultures.Â